PORÓWNANIE ZYGMUNTA III Z WŁADYSŁAWEM II JAGIEŁŁĄ - Przemysław Szpaczyński (In Gremium. Studies in History, Culture and Politics, 2013)
The comparison of Sigismund III to Władysław II JagiełłoThe comparison of Sigismund III to Władysław II Jagiełło, far too more reaching that this one which 150 years ago was superficially done by Antoni Morzycki and which barely signalised unfair historian judgement, may definitely help to understand both policy and aspirations by the great monarch and help to denounce the suffering in historiography stereotypes and prejudices concerning his figure and his reign.In Poland both Sigismund III and Władysław II Jagiełło ruled for almost half a century, in almost 200 years interval. The Polish-Swedish Union like the Polish-Lithuanian Union that took place 2 centuries earlier opened new perspectives. Its main reasons, from the point of view of Sigismund were identical with Jagiełło’s expectations. The first of these reason was to gain help to conquer Moscow. Sigismund III on ascending the Polish throne, as a Swedish monarch with the help and in accordance with his father’s – the King of Sweden John III expectations, meant to take power in Kremlin having carried out a partial partition of the Moscow’s state. Much the same Jagiełło ascending the throne of Poland meant to implement his father’s Olgierd plans to centralize under the power of the Grand Duke of Lithuania the whole of Rus area including Vladimir on the Klyazma River and Moscow itself.The second reason behind the creation of the Union with Poland was, for  Sigismund just like for Jagiełło 2 centuries earlier, to gain additional power to overcome opposition in his hereditary state. Sigismund becoming the king of Poland did not diminish his power in Sweden, but alike 200 years earlier Jagiełło in Lithuania, he enlarged his reign with new territory. They both believed that they would gain armed forces and royal authority to restrain respectively Sigismund – uncle in Sweden and Jagiełło – his relatives in the area of Lithuania and Rus.The third reason was growing in power Prussia, which Sigismund III wanted to include to Poland, which corresponds to the planned at the times of Jagiełło Polish-Lithuanian treat with the Teutonic threat. In both cases expectations were faced with brutal reality.The Polish-Lithuanian Union alike the Polish-Swedish Union changed for a few centuries the fate of few Central-Eastern European nations. The chances, however, which were created by the Polish, the Lithuanian, the Swedish and the Finnish people respectively against Władysław II Jagiełło and the grandson of his grandson – Sigismund III were left not only unused but wasted. It is best proved by the partition of Polish-Lithuanian Republic that took place together with the end of ‘season’ of Swedish power and its loss of Finland in the interest of Russia.